2004
DOI: 10.1300/j052v23n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Education in Six Congregate Meal Sites Improves Participant's Nutrition Knowledge

Abstract: Providing relevant nutrition education at federally funded senior centers is one way of increasing nutrition knowledge of older adults. The purpose of this study was to present three nutrition education sessions on the revised Food Guide Pyramid, dietary protein, and dietary fiber to older adults at six senior centers in Atlanta, Georgia. Three 20-minute lesson plans were developed and delivered at six senior centers over the course of 3 weeks. Forty-eight matched pre- and post-nutrition knowledge tests were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Despite a relatively small sample size, we have demonstrated the success of this program in improving nutritional behavior (fruit and vegetable consumption) and the essential role of peer mentors. We were pleased to note the significant improvement in fruit and vegetable behavior since it is well-established that nutrition education efforts, particularly those that employ computer-generated tailored messages, can be beneficial in this regard [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a relatively small sample size, we have demonstrated the success of this program in improving nutritional behavior (fruit and vegetable consumption) and the essential role of peer mentors. We were pleased to note the significant improvement in fruit and vegetable behavior since it is well-established that nutrition education efforts, particularly those that employ computer-generated tailored messages, can be beneficial in this regard [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…nutritional risk can be a marker for a rapid decline in nutritional status, which can lead to numerous negative health outcomes. Studies have shown that older adults can benefit from nutrition education and counseling (8,12,17).…”
mentioning
confidence: 99%
“…Given the importance of proper nutrition for optimal health, availability of nutrition education at the sites and encouragement to participate are warranted. Nutrition education in congregate meal sites has been found to improve attendee’s knowledge of healthy eating [17]; however, interventions that successfully change eating behavior have not been reported to date. If nutrition education were available on a continuous basis at congregate meal sites with strategies to reach diverse attendees, longitudinal measures of fruit and vegetable consumption may be more promising.…”
Section: Discussionmentioning
confidence: 99%